Factorial invariance of the generalized anxiety disorder scale (GAD-7) in Latin America and the Caribbean - Norman López; Norman López; Juan-Carlos Coronado; Daniela Ripoll-Córdoba; Nicole Caldichoury; César Quispe-Ayala; Breiner Morales-Asencio; Raúl Quincho-Apumayta; Cesar Castellanos; Juan Martínez; Juan Cárdenas-Valverde; Luis Mario Castellanos-Alvarenga; et al. (Frontiers in Psychiatry)
IntroductionThe prevalence of Generalized Anxiety Disorder (GAD) has increased rapidly, highlighting the importance of its detection using quick tools applicable to men and women from different countries.ObjectiveTo analyze the psychometric properties of the Generalized Anxiety Disorder Test (GAD-7) by gender and country in Latin America and the Caribbean (LAC).MethodA cross-sectional e-health study with 12,124 participants from 15 LAC countries (54.32% women, 45.68% men) was conducted, including participants from Argentina (7.3%), Bolivia (6.7%), Colombia (10.3%), Chile (6.9%), Costa Rica (4.9%), El Salvador (5.7%), Ecuador (7.2%), Guatemala (4.7%), Panama (5.1%), Paraguay (5.7%), Peru (8.6%), Puerto Rico (5.8%), the Dominican Republic (6.6%), Uruguay (6.3%), and Venezuela (8.2%). All participants completed the GAD-7 scale digitally.ResultsA unidimensional structure of the GAD-7 was confirmed, explaining 70% of the variance. The model fit indices were adequate (RMSEA = 0.062; CFI = 0.997; TLI = 0.995; SRMR = 0.017; p < 0.001), and the factor loadings for each item were satisfactory (> 0.70). Additionally, the factor structure showed measurement invariance between genders and countries, with adequate fit indices at all levels (configural, metric, scalar, and strict), suggesting that the measurements are equivalent in both contexts. Finally, the internal consistency of the GAD-7 was high, with a McDonald’s Omega coefficient of 0.91.ConclusionsThe GAD-7 exhibits a factor structure that is equivalent across genders and countries, demonstrating its validity and reliability for the rapid detection of GAD symptoms in different countries within the region.